Lughah al-Hayawānāt: Dirāsah Naẓariyyah fī Manẓūr ‘Ilm al-Lughah al-Nafsī (Animal Language: Theoretical Study from Psycholinguistics Perspective) - Khozaimah Khozaimah; Muflihah Muflihah (IAIN MADURA, 2020)
Living with others is not only experienced by humans but also by animals. Animals also use a communication system that enables them to work together. However, their communication system is different from humans. This difference is based on specific characters distinguishing a language from that of other social creatures. This manuscript aims to describe the difference between human and animal language. Specifically, it would discuss basic differences in how animals communicate with others and humans. By using the descriptive analysis method through comparing the resulting data with the current knowledge and relevant literature, the author found some of the basic differences between human and animal's language and the way they communicate, One of the basic differences is “productivity”. Humans can create new expressions or new vocabularies continuously to describe any unlimited new object or situation. They, further, can talk about future and goals while animals don't do so. The second difference is “duality”. Human's language has two types of system, namely meaningless voice and a compound of voice elements which create meaning. Animals, on the other hand, are incapable to produce or compound differences voice to a different meaning.